2021
DOI: 10.3389/fpubh.2020.575145
|View full text |Cite
|
Sign up to set email alerts
|

Nowcasting and Forecasting the Spread of COVID-19 and Healthcare Demand in Turkey, a Modeling Study

Abstract: Background: This study aims to estimate the total number of infected people, evaluate the effects of NPIs on the healthcare system, and predict the expected number of cases, deaths, hospitalizations due to COVID-19 in Turkey.Methods: This study was carried out according to three dimensions. In the first, the actual number of infected people was estimated. In the second, the expected total numbers of infected people, deaths, hospitalizations have been predicted in the case of no intervention. In the third, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Centers for Disease Control and Prevention, 2022a). Unlike COVID-19, mpox is a disease known to be endemic in West and Central Africa for decades; it is caused by monkeypox virus (MPXV), a zoonotic orthopoxvirus (Beer and Rao, 2019). Classical symptoms involve fever, headache, muscle aches, fatigue, lymphadenopathy, and rash(U.S. Centers for Disease Control and Prevention, 2022e).…”
Section: Introductionmentioning
confidence: 99%
“…Centers for Disease Control and Prevention, 2022a). Unlike COVID-19, mpox is a disease known to be endemic in West and Central Africa for decades; it is caused by monkeypox virus (MPXV), a zoonotic orthopoxvirus (Beer and Rao, 2019). Classical symptoms involve fever, headache, muscle aches, fatigue, lymphadenopathy, and rash(U.S. Centers for Disease Control and Prevention, 2022e).…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of the virus depends mainly on airborne dissemination and the vulnerability of dental practitioners [2,10,11]. It was shown that healthcare workers, especially dentists, should be considered in high-risk groups worldwide [12]. However, little is known about the epidemiology of COVID-19 among dentists in developing countries such as the Iraqi Kurdistan Region.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries are using a combination of containment and mitigation activities to stem the progression of SARS-CoV-2 and thus, manage the demand for hospital beds 14 . Nonpharmacological measures have been shown to be effective in controlling the transmission of COVID-19 [15][16][17][18][19] . They can reduce the impact on the healthcare system, giving managers time to properly organize the system.…”
Section: Introductionmentioning
confidence: 99%
“…Nowcasting approaches try to estimate the number of a given event in the present 13,15,22 . This strategy has been used to improve surveillance of infectious diseases like AIDS 23,24 , cholera 25 , influenza infections 13,26 , and recently, COVID-19 3,8,17,20,22,27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation